Matthew Arnold : a literary life (Macmillan, 1998)
Matthew Arnold, the foremost Victorian 'man of letters', forged a unique literary career, first as an important post-Romantic poet and then as a prose writer who profoundly influenced the formation of modern literary and cultural studies